Industrial training report: MARDEC Berhad - Azizan, Azhad (Universiti Teknologi MARA, Perlis, 2024)
It is an honor to complete my internship as a Marketing development intern at MARDEC Berhad, a bachelor's degree applicant. The purpose of this industrial training program, which I am participating in during my last year of education, is to prepare students for the working world by exposing them to it prior to their graduation. To graduate with a bachelor's degree from Universiti Teknologi Mara (UITM), students must finish industrial training. I had given the opportunity to undergo my internship in Marketing department at MARDEC Berhad. All the experiences during my internship include customer engagement, marketing anaylsis, market study and also brand engagement. Other than that, these kind of experiences and knowledges can only get by the internship programme by University Teknologi Malaysia (UITM). This curriculum will help students quickly adjust to a new work environment and get ready to enter a new stage or level of life. In addition, students will be able to apply what they have learned in the classroom to real-world situations. This report served as a means of gathering input from students regarding the training location, assessing their comprehension of the industry, and encouraging reflection on the work completed over the 24-week industrial training program. The training location undergoes a SWOT analysis to assess the company's overall performance in the business, both domestically and globally. Therefore, the findings from SWOT for MARDEC Berhad shows that every company no matter big or small have their own strengths, weaknesses, opportunity and also threat.